Hubungan Body Image, Frekuensi Pemesanan Makanan Online dan Perilaku Makan dengan Status Gizi Remaja Putri Usia 15-18 Tahun di Kelurahan Karet - Alszha Ery Putri (2020)
Adolescents need more nutrients because they affect physical growth and development of body organs so that the food consumed must meet the needs so that there is no nutritional deficiency. Nutritional status is the condition of a person's body as a result of the food consumed and the utilization of nutrients in the body. This study aims to determine the relationship between body image, frequency of online food ordering and eating behavior with the nutritional status of female teenagers aged 15-18 years in Kelurahan Karet. This study used a design cross-sectional with a sample size of 46 respondents using non-probability sampling techniques with method accidental sampling. Data were collected by measuring weight and height, filling out questionnaires and interviews. Bivariate analysis performed using the test chi square. The results of the bivariate analysis showed body image (p = 0.025), frequency of online food ordering (p = 0.484), and eating behavior (p = 1.00) with nutritional status and frequency of online food ordering (p = 1.00) with eating behavior. It can be concluded that there is a relationship between body image and nutritional status, there is no relationship between the frequency of online food ordering and eating behavior with nutritional status and there is no relationship between the frequency of online food ordering and the eating behavior of female teenagers aged 15-18 years in Kelurahan Karet.